2017
DOI: 10.1186/s12891-017-1808-6
|View full text |Cite
|
Sign up to set email alerts
|

Posterior shoulder dislocation with associated reverse Hill-Sachs lesion: treatment options and functional outcome after a 5-year follow up

Abstract: BackgroundThe current study describes several surgical techniques for the treatment of the reverse Hill - Sachs lesion after posterior shoulder dislocation; we also aimed to present long term results followed for a minimum of five years.MethodsThis study is a prospective case series of 17 patients who were treated in our clinic between 2008 and 2011. Patients with a defect size smaller than 25% of the articular surface were treated conservatively. An endoprosthesis of the glenohumeral joint was implanted in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 36 publications
0
31
0
2
Order By: Relevance
“…2,6 In contrast, PSD are relatively rare and occasionally present with anterio-medial defect of humeral head "Reverse Hill-Sachs." 7,8 An unusual presentation in this patient was a double lesion. We termed it "Mirror Hill-Sachs" and discussed it further.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…2,6 In contrast, PSD are relatively rare and occasionally present with anterio-medial defect of humeral head "Reverse Hill-Sachs." 7,8 An unusual presentation in this patient was a double lesion. We termed it "Mirror Hill-Sachs" and discussed it further.…”
Section: Introductionmentioning
confidence: 73%
“…Majority of shoulder dislocations are anterior displacements with postero‐lateral humeral defect known as “Hill‐Sachs lesion.” 2,6 In contrast, PSD are relatively rare and occasionally present with anterio‐medial defect of humeral head “Reverse Hill‐Sachs.” 7,8 An unusual presentation in this patient was a double lesion. We termed it “Mirror Hill‐Sachs” and discussed it further.…”
Section: Introductionmentioning
confidence: 86%
“…In athletes, authors tend to be a bit more aggressive in terms of surgical procedures. Guehring et al[ 69 ] additionally considers the time interval between trauma and surgery. Conservative therapy is a reasonable initial treatment, as one study demonstrated a subjective improvement after 6 mo in 70%-89% of patients.…”
Section: Shoulder Joint Complex In Posterior Shoulder Dislocationmentioning
confidence: 99%
“…Also, an rHSL has significant cartilage involvement and can compromise up to 45° of the articular surface of the humeral head. 7 , 10 In isolation, outcomes of both reconstruction of rHSLs and arthroscopic repairs of circumferential lesions of the glenoid labrum have demonstrated improvement in objective and subjective measures 9 , 11 and no difference in shoulder stability and function when compared to anterior labral repair alone. 12 To date, no outcomes have been reported on the simultaneous treatment of rHSLs and circumferential labral lesions.…”
mentioning
confidence: 99%